O equilíbrio da tributação sobre a renda e sobre o consumo para o alcance de um bem-estar social mínimo - Madeira, Maira Cristina Santos (2023)
This research aims to explore a tax structure that balances income and consumption taxation vis-a-vis efficiency and fairness in the Brazilian tax system; by reducing the tax burden that individuals bear, a factor that impacts their choices and negatively affects the welfare state. Based on the theory of the second best of optimal taxation, this paper intents to demonstrate that it may be possible to reach a progressive tax system using both tax features: income and consumption. That takes into consideration the economic capacity of each person in order to decrease the inequality of society and reach the welfare state. Our understanding is that income and consumption taxation can and must be designed in a harmonious way to create an efficient and fair tax collection system respecting the ability to pay of individuals. The analysis of the income tax is made by segregating the income arising from work and capital - invested or inherited - presenting a conclusion regarding the current Brazilian tax system and its supposedly progressive structure. From the point of view of the consumption tax, this work analyzes the regressivity inherent to the current taxation structure relating to goods and services in Brazil and the essentiality method currently adopted to reduce the negative impacts of taxation on the behavior of the individuals. Pursuant to the results of the research, it will be proposed a balanced taxation system between income and consumption to decrease the impact of the tax burden on the behavior and choices of individuals and, to the extent possible, reach a welfare state.